Insulin Therapy A Pocket Guide - Strachan, Mark W. J. (Springer London : Imprint: Springer, 2013)
Diabetes is extremely common, with approximately 171 million people affected worldwide. The majority of people with diabetes are cared for in primary care. Primary health care professionals are usually adept at dealing with the lifestyle measures and tablet treatments for diabetes, but generally have limited expertise in the initiation and management of insulin therapy. Insulin therapy has also become more complex, with numerous different forms of insulin and more complex delivery devices available. In a secondary care setting, approximately 10% of in-patients will have diabetes at any one time. People with diabetes stay in hospital longer than people without diabetes, and the condition is often poorly managed during in-patient stays, often leading to clinical errors. Insulin Therapy: A Pocket Guide provides clear and concise information about the safe prescribing of insulin both subcutaneously and intravenously. It covers the different types of insulin, the delivery devices, side effects of insulin and, most importantly, guidance on rational dose adjustment. This book is an invaluable guide for general practitioners and primary care nurses with a special interest in diabetes, as well as junior hospital doctors and specialist medical trainees, advanced nurse practitioners and new diabetes nurse specialists.